The Impact Of Time Management And Strategic Planning On Employee Performance Through Self-efficacy In The General Office Of The Ministry Of Interior In The United Arab Emirates - Ali Mohamed Hamad Mohamed Almansoori; Ibrahim Fahad Sulaiman (OCERINT- International Organization Center of Academic Research, 2024)
Volume: 8 Issue: 24 (page: 764 - 784)